Non-surgical management of recurrent Paget's disease of the vulva: A case report - Emily Coffey-Noriega; Hannah Kennedy; Floor J. Backes (Elsevier, 2024)
Paget's Disease of the Vulva is a relatively rare condition with a high rate of recurrence. Extensive work-up and treatment is warranted as lesions have the capacity to become invasive and can be associated with underlying malignancy. First line therapy includes surgical resection. For those that are not surgical candidates or who do not desire surgical intervention, non-surgical management options include topical therapy with imiquimod. Unfortunately, irritating side effects often results in poor treatment compliance and premature discontinuation limiting efficacy. Here we present a unique case of extensive, recurrent vulvar Paget's disease with excellent response to a combination therapy of imiquimod and Silver Sulfadiazine. To the best of our knowledge, this is the first documented case illustrating the utility of non-surgical management with combination therapy with topical imiquimod and Silver Sulfadiazine for treatment in patients who do not desire surgical intervention.